Effect of nitrobenzene on the growth and yield of rice (Bangladesh Rice Journal, 2023)
A field experiment was conducted at two locations (Gazipur and Satkhira) during the Boro (dry) season in 2020 to study the performance of Nitrobenzene on the growth and yield of rice. Four different concentrations of Nitrobenzene (2.0 mL L-1, 2.5 mL L-1, 3.0 mL L-1 and 3.5 mL L-1) as foliar spray with recommended chemical fertilizer (RF) were tested on BRRI dhan89 under wetland condition. Application of Nitrobenzene at different concentrations with RF showed significant effect on rice growth and yield. At both locations, foliar application of Nitrobenzene (2 mL L-1) + RF gave higher number of tiller/m2, panicle/m2 and grain/panicle over RF. At Gazipur site, Nitrobenzene (2 mL L-1) + RF resulted in significant increase of grain and straw yield of BRRI dhan89 over the RF only whereas, at Satkhira site, no significant yield benefit with Nitrobenzene was found over RF. In terms of rice growth, yield and economic point of view, foliar application of Nitrobenzene at low concentration (2 mL L-1) with recommended fertilizer showed positive effect on the growth and yield of BRRI dhan89 in this study. However, since Nitrobenzene is a new type of plant stimulant, detailed studies on its mode of action, interaction with other plant growth hormones and environmental effects are required to get an insight on rice response to Nitrobenzene and its widespread application in rice cultivation.Bangladesh Rice J. 26 (2): 63-72, 2022